2014
DOI: 10.1542/peds.2013-1545
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Bioenergetics and Impaired Immune Response in Granulocytes From Children With Autism

Abstract: Despite the emerging role of mitochondria in immunity, a link between bioenergetics and the immune response in autism has not been explored. Mitochondrial outcomes and phorbol 12-myristate 13-acetate (PMA)-induced oxidative burst were evaluated in granulocytes from age-, race-, and gender-matched children with autism with severity scores of $7 (n = 10) and in typically developing (TD) children (n = 10). The oxidative phosphorylation capacity of granulocytes was 3-fold lower in children with autism than in TD c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 76 publications
(95 reference statements)
5
80
0
Order By: Relevance
“…A role for mitochondrial dysfunction has emerged as a common mechanism underlying many neurological disorders [8, 12, 4143] including ASD [15, 18, 44] with specific detrimental outcomes, such as lower ATP production, increases in mitochondrial ROS, and/or metabolite-inhibition of critical steps within mitochondrial pathways [45]. In this study, we tested for bioenergetics in fibroblasts from carriers of the premutation before a significant clinical involvement was observed.…”
Section: Discussionmentioning
confidence: 99%
“…A role for mitochondrial dysfunction has emerged as a common mechanism underlying many neurological disorders [8, 12, 4143] including ASD [15, 18, 44] with specific detrimental outcomes, such as lower ATP production, increases in mitochondrial ROS, and/or metabolite-inhibition of critical steps within mitochondrial pathways [45]. In this study, we tested for bioenergetics in fibroblasts from carriers of the premutation before a significant clinical involvement was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of this enzyme is decreased in granulocytes and lymphocytes of autistic children contributing to a spectrum of mitochondrial malfunction in these cases [273,274].…”
Section: Cosmetic Ingredients Targeting Autism Genesmentioning
confidence: 99%
“…Although ASD is traditionally described as a developmental disorder of the central nervous system, emerging evidence suggests that systemic physiological abnormalities, including dysregulated inflammation and immune system [6,7], elevated oxidative stress [8], and mitochondrial dysfunction [912], are present in peripheral tissues as well as in brains of autistic patients [13]. Epidemiological studies also identified a staggeringly high comorbidity between ASD and mitochondrial disorder (MD) [14].…”
Section: Introductionmentioning
confidence: 99%